Solving Blasius equation using semi analytic iterative method / Nurul Atikah Halmi and Nur Azyyati Ayob - Halmi, Nurul Atikah; Ayob, Nur Azyyati (2018)
The semi analytic iterative method was applied in this research to solve two forms of Blasius equations. Blasius equation is known as a basic unsolidified dynamics equation. Many methods were approached to solve this problem but a new method has been conducted to resolve this difficulty which is semi analytic iterative method (SAIM). Variational iterative method (VIM) and Iteration method existing results was chosen to be compare with SAIM expectation outcomes. To manage the boundary condition at finite, Pade approximations and simple series approximations are combined m first fonn and second fonn of Blasius equation from that a series solutions was obtained. Based on the algorithm, the most accuracy and efficiency results were successfully demonstrate